Transgenerational phenotypic plasticity: can parental host plant experience affect the phenotype of the offspring? : a study in behavior and physiology in Spodoptera littoralis - Rösvik, Axel (SLU/Dept. of Biosystems and Technology (from 130101), 2015)
The Darwinian theory of natural selection first popularized by Charles Darwin in the mid-19th century has been widely accepted as one of the key mechanisms of evolution. However, before Darwin other scientists such as Jean-Baptiste de Lamarck had their theories about evolution. Lamarck’s theory of inheritance of acquired characteristics was one of these theories and it has today been reexamined as transgenerational epigenetics. In this study we will investigate in the polyphagous moth Spodoptera littoralis (Lepidoptera: Noctuidae) the potential for transgenerational epigenetic inheritance, or transgenerational phenotypic plasticity (TPP), as it will be referred to in this thesis. It is known that parental experience can alter the phenotype of the offspring and therefore increase its fitness in the environment experienced by the parent. In this study, we will test if parental plant experience can affect the behaviour and physiology of second-generation individuals of S. littoralis, in preference, migration and performance bioassays. We found evidence of parental effect in the performance of offspring reared on the same diet as the parent. Interesting trends in the behaviour were also found but no significant difference showing transgenerational modulations of offspring behaviour were shown. Further studies are needed to understand the mechanisms underlying TPP in S. littoralis.